2015
DOI: 10.1038/srep14391
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal tracking of single live cancer cells to understand cell cycle effects of the nuclear export inhibitor, selinexor

Abstract: Longitudinal tracking is a powerful approach to understand the biology of single cells. In cancer therapy, outcome is determined at the molecular and cellular scale, yet relationships between cellular response and cell fate are often unknown. The selective inhibitor of nuclear export, selinexor, is in development for the treatment of various cancers. Selinexor covalently binds exportin-1, causing nuclear sequestration of cargo proteins, including key regulators of the cell cycle and apoptosis. The cell cycle e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 54 publications
7
34
0
Order By: Relevance
“…2B). Consistent with previous studies, this effect on single-cell spatiotemporal dynamics was rapid, as the apparent difference was noticeable as early as 1 h following treatment, reflecting an accumulation of S/G2-M cells (Vassilev et al, 2006;Marcus et al, 2015). Automated single-cell duration measurement showed that the increase in the S/G2-M population was correlated with the residence time in the green phase (representing this population), the latter also exhibiting a dose-dependent trend (Fig.…”
Section: Automated Extraction Of Fastfucci Time-lapse Datasupporting
confidence: 69%
See 1 more Smart Citation
“…2B). Consistent with previous studies, this effect on single-cell spatiotemporal dynamics was rapid, as the apparent difference was noticeable as early as 1 h following treatment, reflecting an accumulation of S/G2-M cells (Vassilev et al, 2006;Marcus et al, 2015). Automated single-cell duration measurement showed that the increase in the S/G2-M population was correlated with the residence time in the green phase (representing this population), the latter also exhibiting a dose-dependent trend (Fig.…”
Section: Automated Extraction Of Fastfucci Time-lapse Datasupporting
confidence: 69%
“…Although the ambiguity might have stemmed from interline variation, the understanding so far has been drawn from cell-population-based experiments, phase-contrast images or low-content microscopy, precluding the precise discrimination between cells that die in mitosis and cells that die following a mitotic attempt. More recently, several qualitative studies using FUCCI-expressing cells have reported the emergence of CDT1 expression following prolonged mitosis (Honda-Uezono et al, 2012;Kaida et al, 2011;Marcus et al, 2015). Through indepth single-cell analyses, we found this phenomenon to be far more common than previously implied.…”
Section: Discussionmentioning
confidence: 55%
“…These compounds are termed selective inhibitors of nuclear export (SINE) and their anti-cancer effects are currently under investigation 31,32 . SINE treatment results in strong cell cycle phenotypes and cell death 33,34 . This example shows a cell that progresses through G1-phase with normal kinetics (approximately 6 hours), but experiences delay in S-phase progression as indicated by the period with both red and green signal (approximately 3 hours in control but 10 in SINE treated).…”
Section: Representative Resultsmentioning
confidence: 99%
“…Additionally, there are small molecules that block the ubiquitination of p53 via inhibition of the E3-ubiquitin ligase MDM2 (HDM2), namely nutlin-3a [12]. Nuclear accumulation of p53, cell cycle effects, apoptosis, and senescentlike growth arrest are noted after treatment of cells with selinexor [13][14][15] or nutlin-3a [12,16], consistent with the involvement of p53. Some studies indicate cancer cells with mutated TP53 show response to treatment with SINE, and others report that the response shows some p53-dependence [14,15,17].…”
Section: Introductionmentioning
confidence: 93%
“…To follow cell loss directly over time we used longterm time-lapse microscopy and longitudinal tracking after treatment with 1 μM selinexor; 1 μM provides nearly maximal effects (Figure 1), has been used extensively in vitro [8,13,17], and is relevant in patients [24,37]. TP53-matched HT-1080 and MCF7 cell lines expressing FUCCI are used; HCT116 FUCCI cells lines could not be obtained due to poor degradation of the G1-phase indicator peptide, mKO2-hCdt1 (30/120).…”
Section: Cells Without P53 Die Faster After Treatment With Selinexormentioning
confidence: 99%